IMPLEMENTASI PROGRAM E-LEARNING MELALUI STRATEGI PENINGKATAN PERAN DAN FUNGSI KUALITAS PENDIDIKAN UNTUK MENDUKUNG S’DGS DI KOTA SURABAYA - Risma Mei Karunia; Ade Maeda Rani; Samsul Arifin (Sintesa, 2023)
This research in the background by education quality in Indonesia is still low, to increase education quality in Indonesia especially in Surabay city, so need to do something innovation education system by Department of education ofSurabaya city, that is by implementing education based on e-learning. E-learning is education system in learning method based on electronic.The main purpose of yhis research is (1) for knowing the role and function e-learning to support education quality in Surabaya city and (2) for analyzing policy that need to do by Surabaya government especially Department of education of Surabaya city in order to improve the role and function e-learning, in the implementation of quality education of junior high school. The location researched is SMP Negeri 23 Kedung Baruk Barat, Rungkut Surabaya.This reaserch is conducted with descriptive qualitative approach describe and interpret phenomenon results of data from field research findings. Data collection techniques used in this research is observation techniques, interview and documentation. This researc use implementing concep and theory used is Greandle theory.